The Role of General Principles of Good Governance (AUPB) in Administrative Court Dispute Resolution - Annura Nazwa; Azmi Fauziah Suanda; Dewi Mayang; Yoga Ammar Arifin; Taufiq Alamsyah (Anthroposia: Journal of Social and Human Development, 2026)
This study examines the role of the General Principles of Good Governance (AUPB) in the resolution of administrative court disputes in Indonesia through a normative legal research approach based on statutory, conceptual, and case analyses. The research analyzes administrative court decisions issued between 2020 and 2023 together with relevant legislation governing administrative justice and government administration. The findings indicate that AUPB has evolved from a complementary interpretative standard into a substantive judicial benchmark for assessing the legality and legitimacy of administrative actions. Judicial application demonstrates that governance principles are utilized across diverse categories of disputes, including licensing, land administration, environmental governance, public information, taxation, procurement, and civil service matters, with varying review orientations reflecting the characteristics of each dispute. The study also reveals regional variations in judicial interpretation and application, producing differences in decision consistency, legal certainty, executorial effectiveness, and public trust. Despite these variations, explicit reliance on AUPB strengthens judicial reasoning, enhances administrative accountability, and promotes more responsive administrative justice. The research concludes that AUPB functions as a central normative instrument for improving adjudicative quality and reinforcing good governance within Indonesia’s administrative law system.